(3TQM bUjOI OYHd GdNRGYis - (3dceGd GdOjf eMeO Hf YR GdOjf eMeO GdfShi GdaGQSis; (3eYjf GdOjf GdaGQSj GdaShj , ceGd GdOjf eMeO Hf YR GdOjf eMeO, GdaShj GdaGQSjs
(3ChdgG (B:s
(3CeG HYO ajbhd CMhL GdeQHhHjf Edi Yah QHg eMeO GdeOYh ceGd GdOjf Hf eMeO ddOYhg HYO GdOjf GdaShi GdaGQSi CaGV Gddg JYGdi Ydjge SLGd Yahg hZaQGfg s
(3BNQgG (B:s
(3hGddg JYGdi CMeO Ydi MSf Jhajbg hEjGg SHMGfg CSCd eSJTaYkG dge Cf jLYd GdTQM hSGFQ CehQi NGdUg dhLgg s
(3GdTGYQ gh CHh Ydi OYHd Hf Ydi Hf QRjf GdNRGYi GdeJhai (B246 (3g` hGdbUjOg JGFjg ai efGbH Cd GdHjJs
(3CdagG ai CUHgGf Sfg (B1102 " (3GdTGQM (B"s
(3GdbUjOI eTchdIs
(3HBNQ UaMGJgG JYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
Keywords: (3GdCOHs